On the Telemedicine Microcontroller-Based ECG Security Using a Novel 4Wings-4D Chaotic Oscillator (N4W4DCO) - Borel Dilane Banmene Lontsi; Gideon Pagnol Ayemtsa Kuete; Justin Roger Mboupda Pone (IET Circuits, Devices and Systems)
In this contribution, a chaos-based microcontroller electrocardiogram (ECG) signal acquisition-security-transmission system is proposed. It is designed based on a Novel 4Wings-4D Chaotic Oscillator (N4W4DCO) with a hyperbolic sine nonlinearity unbalanced. The classical nonlinear dynamics tools, such as 2D bifurcation and the highest Lyapunov exponent curves, basins of attraction, and power spectral density, help us see that the proposed chaotic oscillator generates periodic oscillations, intermittency + crisis routes to chaos, transient chaos, and the coexistence of 4/2 wings attractors just to name a few dynamics. The data generated using highly chaotic regime are tested using the well-known NIST TEST -800-22 Rev A and the results passed the test successfully. The N4W4DCO oscillator is embedded in an Arduino microcontroller where the discovered interesting dynamics are confirmed. A low-cost ECG acquisition circuit with an AD8232 ECG sensor is also designed and experimented. ECG signals are acquired and directly loaded into MATLAB-Simulink and are successfully encrypted with random data from the N4W4DCO in its chaos regime. The scrambled ECG signals from experiment are sent through an added white gaussian noise (AWGN) channel and thereafter received and decrypted. These results are promising and open the possibility of improving secure telemedicine transmission systems.